Plasmacytoid dendritic cells contribute to vascular endothelial dysfunction in type 2 diabetes - Alluri, K.; Srinivas, B.; Belmadani, S.; Matrougui, K. (Frontiers in Cardiovascular Medicine, 2023)
Objective Type 2 diabetes (T2D) is associated with an increased risk of cardiovascular disease due to macro- and microvascular dysfunction. This study aimed to investigate the potential involvement of plasmacytoid dendritic cells (pDCs) in T2D-related vascular dysfunction. Approach and results pDCs were isolated from db/db and control mice. It was found that pDCs from db/db mice impaired endothelial cell eNOS phosphorylation in response to ATP and decreased vascular endothelium-dependent relaxation compared to pDCs from control mice. Moreover, isolated CD4+ cells from control mice, when stimulated overnight with high glucose and lipids, and isolated pDCs from db/db mice, display elevated levels of ER stress, inflammation, and apoptosis markers. Flow cytometry revealed that pDC frequency was higher in db/db mice than in controls. In vivo, the reduction of pDCs using anti-PDCA-1 antibodies in male and female db/db mice for 4 weeks significantly improved vascular endothelial function and eNOS phosphorylation. Conclusion pDCs may contribute to vascular dysfunction in T2D by impairing endothelial cell function. Targeting pDCs with anti-PDCA-1 antibodies may represent a promising therapeutic strategy for improving vascular endothelial function in T2D patients. This study provides new insights into the pathogenesis of T2D-related vascular dysfunction and highlights the potential of immunomodulatory therapies for treating this complication. Further studies are warranted to explore the clinical potential of this approach.